Development of Piezoelectric-Based Energy Harvesting Device for Smart City Applications - Mazlan, Nurul Shafika (2018)
Smart city uses sensor to collect data to be used in managing asset and resources. There are many components in the smart city include smart parking system. Traffic congestion have become a problem especially in popular places like the shopping mall as there are too many cars and less parking. Sensors are needed to track the amount of parking space. To adopt the smart city concept, the element of non-renewable energy sources like fossil fuel and battery need to be minimized and replaced with renewable energy. To power up the sensor for smart city application, energy harvesting device, piezoelectric energy harvester is adopted to convert vibration to electricity. This research is carried out to understand the feasibility of utilizing the energy harvesting method to power up the sensor for smart city application. The project starts with doing simulation with MATLAB Simulink to know the characterization of the piezoelectric. The prototype is develop to test the piezoelectric cantilever beam in order to harvest energy.